Health Belief Model and PRECEDE PROCEED on the Risk Factors of Multidrug Resistant Tuberculosis in Surakarta, Central Java - Vera -; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2017)
Background: Tuberculosis (TB) is one of the lethal infectious diseases in the world. One of the current biggest challenges of Tuberculosis control is the widespread emergence of Multidrug Resistant Tuberculosis (MDR-TB). There are several potential risk factors of MDR-TB that can be explained by Health Belief Model and PRECEDE PROCEED model framework. This study aimed to analyzed factors associated with MDR-TB using Health Belief Model and PRECEDE PROCEED.Subjects and Method: This was an analytic observational study with case control design. The study was conducted at Dr. Moewardi Hospital and BBKPM, Surakarta, from September to November 2017. The study subjects were selected using fixed disease sampling, consisting of 76 MDR-TB patients and 228 TB patients. The dependent variable was MDR-TB. The independent variables were educational level, self-efficacy, drug-taking adherence, smoking, nutritional status, perceived of susceptibility, perceived barrier, perceived severity, perceived benefit, and drug-taking supervisor. The data were collected using questionnaire and analyzed by path analysis. Results: The risk of MDR-TB was increased by lack of drug-taking adherence (b= -1.69; 95% CI= -2.28 to -1.09; p <0.001), poor nutritional status (b= 1.32; 95% CI= 0.72 to 1.92; p<0.001), and smoking (b= 1.32; 95% CI= 0.72 to 1.92; p <0.001). Drug-taking adherence was increased by perceived susceptibility (b= 0.91; 95% CI= 0.18 to 1.63; p=0.015), perceived severity (b= 1.01; 95% CI= 0.28 to 1.74; p=0.007), perceived benefit (b= 1.69; 95% CI= 0.97 to 2.41; p<0.001), drug-taking advisor (b= 2.16; 95% CI= 1.44 to 2.88; p<0.001), self efficacy (b= 1.58; 95% CI= 0.86 to 2.31; p<0.001), and low perceived barrier (b= -1.10; 95% CI= -1.82 to -0.38; p=0.003). Conclusion: The risk of MDR-TB is increased by the lack of drug-taking adherence, poor nutritional status, and smoking.Keyword: Health belief model, PRECEDE-PROCEED, MDR-TBCorrespondence: Vera. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: vera21210@gmail.comJournal of Epidemiology and Public Health (2017), 2(3): 241-254https://doi.org/10.26911/jepublichealth.2017.02.03.06